Prevalence of Helicobacter pylori infection among COVID-19 patients in Baghdad province - Firas Qays Jameel (Genius Journals, 2022)
In recent years Helicobacter pylori consider as a worldwide public health and a social problem in many countries, The cases of H.pylori infection showed a significant increase in our country in last years, some of recent studies highlight on there are correction between H.pylori infection and Gastrointestinal Symptoms in COVID-19 patients This study was aimed to Prevalence of Helicobacter pylori infection among COVID-19 patients in Baghdad province. This study was conducted on 120 patients with COVID-19 Infection and gastrointestinal symptoms, their age 22 to 65 years, in period extended from September 2021 to June 2022 in Medical AL- Imammian AL- Kadhmain City teaching Hospital; Baghdad teaching Hospital And COVID-19 Isolation center. The stool and blood samples of COVID -19 Infection have been collected, Non-invasive test (SAT and Cag-IgG) were evaluated in all patients, CTK.biotech and Assure® H. pylori IgG Rapid tests were used and the result confirmed by PCR
Keywords: Helicobacter pylori,; gastrointestinal symptoms; COVID-19.